2019
DOI: 10.1111/jnc.14870
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics of synaptosome S‐nitrosylation in Alzheimer’s disease

Abstract: Increasing evidence suggests that both synaptic loss and neuroinflammation constitute early pathologic hallmarks of Alzheimer’s disease. A downstream event during inflammatory activation of microglia and astrocytes is the induction of nitric oxide synthase type 2, resulting in an increased release of nitric oxide and the post‐translational S‐nitrosylation of protein cysteine residues. Both early events, inflammation and synaptic dysfunction, could be connected if this excess nitrosylation occurs on synaptic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 106 publications
(128 reference statements)
0
30
0
Order By: Relevance
“…Excessive NO production reported in prion disease, AD, and PD is inducing aberrant posttranslational protein modifications and uncontrolled neurotoxic nitrergic signaling (6)(7)(8)(9). Protein cysteine residues can be directly and reversibly S-nitrosylated by NO (9) which can lead to protein dysfunction to facilitate disease progression (10,11). NO also reacts with free radicals such as superoxide anion O 2…”
mentioning
confidence: 99%
“…Excessive NO production reported in prion disease, AD, and PD is inducing aberrant posttranslational protein modifications and uncontrolled neurotoxic nitrergic signaling (6)(7)(8)(9). Protein cysteine residues can be directly and reversibly S-nitrosylated by NO (9) which can lead to protein dysfunction to facilitate disease progression (10,11). NO also reacts with free radicals such as superoxide anion O 2…”
mentioning
confidence: 99%
“…The induction of nitric oxide synthase type 2 leads to increased nitric oxide levels and S -NO of cysteine residues ( Paula et al, 2010 ). An isobaric tag approach, iodoTMT, was used to reveal the S -NO sites on Cys residues of NOS2-dependent S -NO of synaptic proteins in mild cognitive impairment (MCI) and AD and human control brain tissues ( Wijasa et al, 2020 ). Of 291 and 295 S -NO proteins identified in synaptosome fractions, 16 and 9 S -NO proteins were significantly increased in AD vs. MCI brains and AD vs. Ctrl, respectively ( Wijasa et al, 2020 ).…”
Section: Cysteine Oxidation In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Most often, such modifications inhibit protein functions. Selected studies of the S-nitrosylation proteome in AD identified key proteins with altered functions associated with antioxidant, glycolysis, mitochondrial export, calcium homeostasis, synapses, apoptosis, mitochondrial dynamics, protein folding, and neuroinflammation, among other functions [ 113 , 114 , 115 , 116 ]. Many of these proteins are the same as those modified by other indices of oxidative and nitrosative stress noted above.…”
Section: Oxidative and Nitrosative Modifications Of Mitochondrial mentioning
confidence: 99%